Smallholder cassava commercialisation: implication for household income among farmers in Oyo State, Nigeria (2015)
"Crop commercialization by smallholder farmers in Nigeria is virtually non-existent due to a range of constraints, thereby affecting the income status of the farmers. This study investigated the effect of agricultural crop commercialization on household income in Oyo state, Nigeria. Data was collected through the use of questionnaires administered to 203 cassava farmersusing a multistage sampling technique. Data collected included demographic characteristics of respondents, cassava production, sales volume and prices analyses carried out on the data were descriptive statistics, Household Commercialization Index (HCl), ordinary least Square regression and probit regression model. The results reveals that majority of the respondents (84.7%) were male. The average age of the farmers was 45 years while the average household size is 6 members. The results of household commercialization index showed that 97% of the crops by the farmers were commercialized the average household commercialization index was 0.9.Regression analysis of determinants of agricultural commercialization revealed three significant variables, namely:(gender (p<0.0I) (β =0.3808)), education (p<0.0l) (β= 0.0529)) and farm size (p<0.0I)β=0.3751)). Analysis of the effect of commercialization on household income revealed four significant variables, which are gender, education, total cassava produced and farm size. The major constraints to full commercialization as ranked in order of importance to the farmers in the study area are: poor road, credit inaccessibility, unattractive market prices, and transaction bottleneck. These findings demonstrated the' need to strengthen policies that encourage effective integrated marketing information, guaranteed market for farm produce, rehabilitation of rural roads and accessibility to credit, ensuring full commercialization. "